1999
DOI: 10.1046/j.1365-313x.1999.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Emission of nitrous oxide (N2O) from transgenic tobacco expressing antisense NiR mRNA

Abstract: SummaryThe emission of N 2 and N 2 O from intact transgenic tobacco (clone 271) expressing antisense nitrite reductase (NiR) mRNA, and wild-type plants grown aseptically, on NO 3 ± , NO 2 ± or NH 4 + -containing medium was investigated. 15 N contents of gas sampled from gassealed pots, in which the plants were grown on 15 Ncontaining medium, were analyzed by gas chromatography and mass spectrometry (GC±MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 23 publications
2
53
0
1
Order By: Relevance
“…The transgenic tobacco used here (line 271) bears chimeric nitrite reductase (NiR) cDNA in an antisense orientation [39] and thus practically lacks NiR activity (less than 5% of the wild type). These tobacco plants were aseptically cultivated on B medium [36] for seven weeks as described previously in [21]. They were then fumigated with 1 or 4 ppm of 15 NO 2 (51.6 atom% 15 N) for five days (fumigation period), after which they were transferred onto a B medium [36] in gas-sealed pots without the addition of NO 2 and the cultivation was continued for three days (emission period).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transgenic tobacco used here (line 271) bears chimeric nitrite reductase (NiR) cDNA in an antisense orientation [39] and thus practically lacks NiR activity (less than 5% of the wild type). These tobacco plants were aseptically cultivated on B medium [36] for seven weeks as described previously in [21]. They were then fumigated with 1 or 4 ppm of 15 NO 2 (51.6 atom% 15 N) for five days (fumigation period), after which they were transferred onto a B medium [36] in gas-sealed pots without the addition of NO 2 and the cultivation was continued for three days (emission period).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they were transferred onto an MS medium in gassealed pots, in which the nitrogen source was replaced by 50 mM non-labelled KNO 3 and the culture was continued for one week (emission period). At the end of the cultivation, gas samples were collected and 15 N 2 O was analysed by gas chromatography-mass spectrometry equipped with a precondensing apparatus (FINNIGAN MAT Instrument Inc., Germany) as previously described [21].…”
Section: Determination Of the Emission Of N 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, evidence shows that soil moisture (Bouwman 1996;Del Prado et al 2006;Du 2006;Li et al 2004), temperature (Bouwman 1996;Du 2006) and grazing (Velthof and Oenema 1997) as well as N fertilization (Del Prado et al 2006;Stehfest and Bouwman 2006;Velthof and Oenema 1997) have a great impact on N 2 O emissions from grasslands. Recent research has identified that some plants have the capacity to emit N 2 O to the atmosphere (Goshima et al 1999;Zhang and Jiang 2006;Zou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This plant accumulated nitrite at least 5-fold over the wild-type (WT) level (Vaucheret et al 1992) and produced N 2 O with increasing nitrite levels in plant tissues (Goshima et al 1999). We used this transgenic line to investigate the consequences of nitrite accumulation on the production of NO AE and derivatives, with particular emphasis on the nitration state of tyrosine residues of proteins.…”
Section: Introductionmentioning
confidence: 99%